Ultra-Widefield OCT Images of Proliferative Vitreoretinopathy under Silicone Oil - Masaki Kinoshita; Susumu Sakimoto; Masaki Suzue; Masanori Kanai; Nobuhiko Shiraki; Kohji Nishida (Case Reports in Ophthalmology)
Introduction: Proliferative vitreoretinopathy (PVR) is a condition in which proliferation forms after rhegmatogenous retinal detachment (RRD) surgery or old RRD, and sometimes, PVR can occur under silicone oil (SO). Here, we report 2 cases of PVR in which we evaluated preoperative B-scan images of proliferation under SO using ultra-widefield swept-source OCT (UWF-SS-OCT). Case Presentation: The first case was a 61-year-old male who presented with PVR under SO tamponade after multiple pars plana vitrectomies (PPVs) at the previous hospital, and the second case was a 23-year-old man patient who was diagnosed with Coats disease in childhood and presented with PVR under SO after PPV for total RRD at our hospital. B-scan images of UWF-SS-OCT provided findings of epiretinal two-layered proliferation or emulsified SO in the peripheral area. Conclusion: UWF-SS-OCT is useful for preoperative assessment of the proliferation of PVR before SO removal. In addition, peculiar proliferation may occur in the eye under SO.